Examining Linkages Between Bereavement Grief Intensity and Perceived Death Quality: Qualitative Findings. (December 2016) - Wilson, Donna M.; MacLeod, Rod; Houttekier, Dirk
Some people experience more intense and prolonged bereavement grief after the death of a loved one. A mixed-methods study was undertaken out of concern that bereavement grief intensity may be associated with survivor perceptions of a "good" or "bad" death. The qualitative study phase was undertaken after a pilot study revealed bereavement grief intensity and perceived death quality were close to being negatively correlated ( R = −.156, p = .06). Through interviewing 41 bereaved volunteers, bereavement was found to be an individualized, contextualized, and multifaceted experience, but with three themes emerging through constant-comparative analysis: (a) the huge loss and enormous gap in life as a result of the death of a loved one, (b) extreme acute grief, and (c) the uncertain step-laddered journey of grieving to bereavement recovery. This recovery is impacted by both good and bad aspects of the death or dying process, as well as good and bad after-death events and developments.